Neutrino masses and interactions from Super-Kamiokande - Lola, S. (HNPS Advances in Nuclear Physics, 2020)
We discuss topics on neutrino masses and interactions, in the light of the Super- Kamiokande data. The experimental observations can be explained either by several patterns of neutrino masses, or byflavour-changingneutrino matter-interactions. In the latter case, the coupling constants of the relevant operators are large enough to give interesting signals in ultra-high energy neutrino scattering to matter.